La estructura de la Diacetonafenantrenoquinona - Constenla Umaña, Manuel Arturo (1971)
The substance, diacetonephenanthrenequinone, long believed to have structure I or II, is found to have structure IV according to modern spectroscopic methods and chemical behavior.